2019
DOI: 10.1111/epi.14646
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time effects of interictal spikes on hippocampus and amygdala functional connectivity in unilateral temporal lobe epilepsy: An EEGfMRI study

Abstract: Summary Objective To explore the real‐time effects of interictal epileptiform discharges (IEDs) on hippocampus and amygdala functional connectivity (FC) in unilateral temporal lobe epilepsy (TLE). Methods Patients with unilateral TLE were recruited and underwent simultaneous electroencephalography–functional magnetic resonance imaging (EEG‐fMRI) scanning. Simultaneous EEG was used to define the prespike (10 s before spike) and postspike (10 s after spike) periods. Dynamic FC analysis was applied using the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Focal epilepsy is associated with brain dysfunction that extends beyond the epileptic network (Bettus et al , 2011; Englot et al , 2016; Lagarde et al , 2018; Tong et al , 2019). This dysfunction may contribute to cognitive impairments in these patients (Hermann et al , 2006) and prime the brain for further spread of the epileptic network (Sato et al , 1998; Velisek and Moshe, 2003), but lack of mechanistic understanding limits approaches to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal epilepsy is associated with brain dysfunction that extends beyond the epileptic network (Bettus et al , 2011; Englot et al , 2016; Lagarde et al , 2018; Tong et al , 2019). This dysfunction may contribute to cognitive impairments in these patients (Hermann et al , 2006) and prime the brain for further spread of the epileptic network (Sato et al , 1998; Velisek and Moshe, 2003), but lack of mechanistic understanding limits approaches to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interictal epileptiform discharges (IEDs) and seizures are pathological hypersynchronous patterns of brain activity that are localized in patients with focal epilepsy (Rosenow and Luders, 2001; Bartolomei et al , 2017). However, neuropsychological, structural and functional indicators suggest that these patients’ brains demonstrate abnormalities that extend beyond the region from which IEDs and seizures can be recorded (epileptic network) (Bettus et al , 2011; Englot et al , 2016; Lagarde et al , 2018; Tong et al , 2019). The mechanisms by which epileptic activity interacts with and shapes these large-scale neural networks in the human brain remain mostly unknown and have implications for associated neuropsychiatric dysfunction and progression of focal epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of IEDs on cognitive networks were not often explored until recently. Following pioneering work relating IED-correlated decreases in Default Mode Network activity in temporal lobe epilepsy (84) and generalized epilepsy (85), recent works have shown the possible impact of interictal activity on several ICNs in focal epilepsy in adults (33, 36, 45), focal epilepsy in children (22), children with idiopathic focal epilepsy [Benign Epilepsy with Centro-temporal Spikes (BECTS)] (53, 55, 86), epileptic encephalopathy (5659), as well as generalized epilepsies (61, 64), including Childhood Absence Epilepsy (CAE) (87), and even reflex epilepsies (60). The majority of recent EEG-fMRI studies who evaluate the interaction between interictal discharges, ICNs, and their relationship to neuropsychological outcome have been in BECTS patients; these studies found a negative correlation between cognitive functioning and Functional Connectivity (FC).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed the spatial pattern can have an influence on which cognitive domain is predominantly affected. For example, in TLE patients the laterality of IED activity can preferentially damage certain cognitive abilities, such that left temporal IEDs were associated with disconnections to the hippocampus and the Default Mode Network (DMN) while right temporal IEDs were co-activated with the reward-emotion network, which could be involved in forced normalization (a condition in which patients show psychiatric degradation when the IEDs disappear under treatment) (45).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, IEDs appear able themselves to induce global network changes (Wilke et al, 2011;Malinowska et al, 2014;Lagarde et al, 2018) , even mediating epilepsyassociated cognitive impairment and affecting normal neurodevelopment in childhood (Kobayashi et al, 2005(Kobayashi et al, , 2006Fahoum et al, 2012;Ibrahim et al, 2014). For instance, large-scale physiological network communication is disrupted by IED-induced oscillations (Dahal et al, 2019), resulting in impaired memory formation (Gelinas et al, 2016;Tong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%